2010
DOI: 10.1063/1.3450321
|View full text |Cite
|
Sign up to set email alerts
|

Global and local instability of flow focusing: The influence of the geometry

Abstract: In the flow focusing technique, a liquid flow rate Q is injected through a microcapillary to form a meniscus attached to its edge. The meniscus is stretched until a thin jet tapers from its tip due to the action of a gas stream driven by a pressure drop ⌬p. Both the liquid jet and the gas stream cross the orifice of a plate located in front of the capillary at a distance H. In the present work, the stability of both the tapering liquid meniscus and the emitted jet is analyzed experimentally. Three regimes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 42 publications
5
80
0
Order By: Relevance
“…When using GDVNs to deliver precious protein samples in SFX experiments, one of the most important parameters is the minimum liquid flow rate, Q min , as it determines the rate of sample consumption and the smallest achievable jet diameter (further discussed in the next paragraph). The study of Vega et al 23 found empirically that the optimum minimum flow rate to produce a jet for low viscosity fluids is given by the relationship…”
Section: Nozzle Geometry Influence On Jet Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…When using GDVNs to deliver precious protein samples in SFX experiments, one of the most important parameters is the minimum liquid flow rate, Q min , as it determines the rate of sample consumption and the smallest achievable jet diameter (further discussed in the next paragraph). The study of Vega et al 23 found empirically that the optimum minimum flow rate to produce a jet for low viscosity fluids is given by the relationship…”
Section: Nozzle Geometry Influence On Jet Characteristicsmentioning
confidence: 99%
“…In previous flow-focusing studies, the energy supplied by the gas flow to the system was described in terms of the gas pressure. 19,23,28 However, we will base our analysis on mass flow because this quantity is conserved throughout the nozzle, regardless if the flow is choked at the exit gas aperture.…”
Section: Characterization Of Nozzle Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In this regime, the dynamics of drop breakup is entirely controlled by the flow rate of the 25 outer phase, 8 such that the drop size depends on the flow rate of the outer phase, 6, 9 its viscosity and surface tension, 10 and the channel geometry. 7,11,12 However, the necking process, which eventually leads to drop formation, is slow, limiting the maximum drop 30 generation frequency and hence the throughput. The drop generation frequency can be increased if an additional thin orifice is added after the crossjunction.…”
Section: Introductionmentioning
confidence: 99%